Pengaruh Perceived Taste Dan Suasana Kafe Terhadap Keputusan Pembelian Dengan Persepsi Nilai Sebagai Variable Mediasi Pada Tomoro Coffee Cabang Dinoyo (Studi Pada Mahasiswa Unisma) - Elly Nafida Faza; Nur Hidayati; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to determine the influence of Perceived Taste and Café Atmosphere on Purchasing Decisions with Perceived Value as a mediating variable among consumers of Tomoro Coffee Dinoyo Branch. This research employed a quantitative approach, with data collected through questionnaires distributed to 101 respondents who had previously purchased products at Tomoro Coffee. The data analysis technique used in this study was Partial Least Square – Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results showed that Perceived Taste significantly affects Perceived Value and Purchasing Decisions. In addition, Café Atmosphere significantly influences Perceived Value but does not have a significant direct effect on Purchasing Decisions. Furthermore, the mediation analysis indicated that Perceived Value fully mediates the relationship between Café Atmosphere and Purchasing Decisions. This finding suggests that the café atmosphere does not directly encourage consumers to make purchasing decisions; instead, consumers’ perceptions of taste and value play a more dominant role in influencing their purchasing decisions toward Tomoro Coffee products and services. In conclusion, Perceived Taste and Perceived Value are more dominant in influencing consumer purchasing decisions than Café Atmosphere directly. The findings of this study imply that improving product taste quality and creating positive perceived value are important strategies for encouraging better purchasing decisions in the coffee shop industry. Keywords: Perceived Taste, Café Atmosphere, Perceived Value, Purchasing Decision, Tomoro Coffee.